Protocolo para screening de habilidades musicais - Koga, Fabiana Oliveira [UNESP] (2019)
The perceptual-sensory musical abilities are at the basis of music talent. Knowing them will allow access to part of this complex phenomenon composed of different nuances in order to contribute to the initial recognition of talented children and young people in music. Unfortunately, there is no music education in all Brazilian schools, even with a federal decree that establishes this, it is low the rate of procedures that are dedicated to the identification, evaluation and enrichment of people with music talent. Based on this context, if the school cooperated with the screening of music talent and direct the identified students to multimodal evaluations or projects and out-ofschool institutions (music schools) or allow the development of music activities inside school (curricular adaptions and groupings) and if music wasn’t understood only as entertainment, many talented students in music would not be at music education’s margin and music professionalization. So a screening for musical abilities built for Brazilian reality, for elementary school, primary education, according to psychophysical method of peer comparison would be able to initially map, revealing music talent cases? Based on these questions, this thesis aimed to build and instrument to screening (mapping) music abilities according to psychophysical method of peer comparison able to map initially music talents. For this purpose, there was initially in Study1 a systematic review around the construct, in Study 2, other to list the properties and component attributes of the construct, then, in Study 3 the construction of the Protocol for Screening Music Abilities. The instrument counts on 127 items distributed in eight dimensions (timbre, height, melody, intensity, harmony, agogic, length and rhythmic pattern). The instrument was submitted to judges specialized in music, applied in pilot project, received amendments and it was finally applied in eight schools from the countryside of São Paulo. 411 students from public schools and 242 students from private schools participated of the empiric application of the instrument. All of them aged from six to 11 years old, enrolled in 1st and 5th grades. The data analysis followed the criteria: converting the answers to scores, analysis of the validity of the instrument through W Kendell, item analysis using chi-square test, binominal test and the students with better and fewer results were identified. The Kruskall-Wallis statistics tests were used to compare the groups and the Wilcoxon test for intergroup analysis. In conclusion, Protocol for Screening Music Abilities was able to screen music talent initially, however, future refining procedures will be necessary to adjust those items that presented problems and even readjust the levels of application, considering the performance of the participants by performance range.